Recent Experience With Multilateral Official Debt Rescheduling, 1987. (World Economic and Financial Surveys; World Economic and Financial Surveys ;, 1986)
This paper describes developments in multilateral official debt renegotiations over the 18 months up to the end of June 1986. To facilitate the return to normal market access for countries considered to have made substantial progress in their adjustment efforts, official creditors recently concluded multiyear rescheduling agreements (MYRAs) with both Ecuador and Cote d'Ivoire. Official creditors have also indicated that they were prepared to grant an extended consolidation period for Yugoslavia, although in this case a further meeting would be necessary to agree on the terms for the second stage of the rescheduling. The tendency toward increased differentiation in terms according to the circumstances of the debtor country, already apparent in 1983-1984, has been carried further during the last 18 months. Indeed, the rescheduling agreements concluded during this recent period tend to fall fairly clearly into two very different groups. Official multilateral debt renegotiations deal with the rescheduling of debt service payments on loans extended by, or guaranteed by, the governments or the official agencies of the participating creditor countries.